Penerimaan Harga Diri Dan Citra Tubuh Santri Putri Sasak Di Pesantren AL-Fatihin Sintang - Zulfah, Arima (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2023)
Abstract: Adolescence is a period when individuals generally have special concerns regarding perceptions of body image. Body image and self-esteem are important issues for adolescents. Teenagers have criteria as to what people are considered physically attractive and in appearance. Every individual has an ideal self-image like what he wants, including what ideal body shape he wants to have. The discrepancy between the body perceived by the individual and the ideal body shape can lead to dissatisfaction with his body. This is closely related to body image, namely how a person perceives and evaluates his own body. The research method uses qualitative research. Techniques and data collection was carried out by in-depth interviews conducted directly by telephony. The results show that body image and self-esteem play an important role in the life of female students of Sasak Al -Fatihin Sintang.